If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + 10p = 36 + 8p Solving 26 + 10p = 36 + 8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8p' to each side of the equation. 26 + 10p + -8p = 36 + 8p + -8p Combine like terms: 10p + -8p = 2p 26 + 2p = 36 + 8p + -8p Combine like terms: 8p + -8p = 0 26 + 2p = 36 + 0 26 + 2p = 36 Add '-26' to each side of the equation. 26 + -26 + 2p = 36 + -26 Combine like terms: 26 + -26 = 0 0 + 2p = 36 + -26 2p = 36 + -26 Combine like terms: 36 + -26 = 10 2p = 10 Divide each side by '2'. p = 5 Simplifying p = 5
| 5x+4=289 | | 6(k+8)+7k=-8 | | 8(-0.5+-0.375x)+4=-3x | | -9(t+6)=18 | | f(x)=20+40 | | 4x=18x | | -2(3t-5)+3t=2t-2 | | 6(x+36)-3(2x+12)=4x-10 | | x^2-14y=0 | | 5b-b=8 | | 3x(5-2x)+4=6 | | 7/12=7/9x | | (1-3x)=-8x+14 | | 2/n=-7 | | 20=a+3 | | x^2=-5y | | 8(x-4)+4(x-8)+(x-3)=2x-1 | | 66+6y-20=16y-10-2y | | Z^3+5z+3z^2+1+4-2z^2= | | 24/25=s/35 | | -10/9i | | 4(n+6)=8-4(n-2) | | 12+p=8+7 | | =x^2+4x | | 2(cos(2pi))=0 | | 4m^5n^0(5m^3)= | | 2/7x234/1 | | 4(2x+-1)=.5(16x+-8) | | ln(3x-2)=2.3 | | 3xwhat=123 | | 12y+10y=20y-3 | | 3(n+8)=3-3(n-7) |